Pengaruh Profitabilitas (ROA) Terhadap Solvabilitas (RBC) Pada Perusahaan Asuransi Kerugian Yang Terdaftar Di Bursa Efek Indonesia - Aulia Rosalinda Septiawati (Journal of Economic, Bussines and Accounting (COSTING), 2023)
Insurance companies help reduce losses that may be incurred by investments as well as for life and asset protection. This study aims to determine the effect of return on assets (ROA) on risk based capital (RBC) in insurance companies listed on the IDX. Quantitative method with the type of associative problem formulation that has a causal relationship as well as secondary data sources in the form of financial reports (annual reports) of insurance companies listed on the IDX are used in this study. The population in this study were 84 insurance companies listed on the IDX and sampling was carried out using a non-probability sampling method with a purposive sampling technique. Descriptive analysis, data normality test, product moment correlation, simple linear regression, t test, and the coefficient of determination are the data analysis techniques used in this study. The results of this study show that profitability (ROA) has a positive and significant effect on solvency (RBC) in general insurance companies listed on the IDX. Keywords: Risk Based Capital, Return on Assets, and Insurance Company.